Long-term complications and implant survival rates after cranioplastic surgery: a single-center study of 392 patients - Giese, Henrik; Meyer, Jennifer; Unterberg, Andreas; Beynon, Christopher (Neurosurgical review, 2021)
Cranioplasty (CP) is a standard procedure in neurosurgical practice for patients after (decompressive) craniectomy. However, CP surgery is not standardized, is carried out in different ways, and is associated with considerable complication rates. Here, we report our experiences with the use of different CP materials and analyze long-term complications and implant survival rates. We retrospectively studied patients who underwent CP surgery at our institution between 2004 and 2014. Binary logistic regression analysis was performed in order to identify risk factors for the development of complications. Kaplan-Meier analysis was used to estimate implant survival rates. A total of 392 patients (182 females, 210 males) with a mean age of 48 years were included. These patients underwent a total of 508 CP surgeries. The overall complication rate of primary CP was 33.2%, due to bone resorption/loosening (14.6%) and graft infection (7.9%) with a mean implant survival of 120 ± 5 months. Binary logistic regression analysis showed that young age (< 30 years) (p = 0.026, OR 3.150), the presence of multidrug-resistant bacteria (p = 0.045, OR 2.273), and cerebrospinal fluid (CSF) shunt (p = 0.001, OR 3.137) were risk factors for postoperative complications. The use of titanium miniplates for CP fixation was associated with reduced complication rates and bone flap osteolysis as well as longer implant survival rates. The present study highlights the risk profile of CP surgery. Young age (< 30 years) and shunt-dependent hydrocephalus are associated with postoperative complications especially due to bone flap autolysis. Furthermore, a rigid CP fixation seems to play a crucial role in reducing complication rates.
Published: 26 August 2020
Gesehen am 01.12.2021